The Impact of Navigation on Proxemics in an Immersive Virtual Environment with Conversational Agents - Connolly, Rose; Buck, Lauren; Zordan, Victor; Mc Donnell, Rachel (IEEE Transactions on Visualization and Computer Graphics, 2025)
As social VR grows in popularity, understanding how to optimise interactions becomes increasingly important. Interpersonal distance—the physical space people maintain between each other—is a key aspect of user experience. Previous work in psychology has shown that breaches of personal space cause stress and discomfort. Thus, effectively managing this distance is crucial in social VR, where social interactions are frequent. Teleportation, a commonly used locomotion method in these environments, involves distinct cognitive processes and requires users to rely on their ability to estimate distance. Despite its widespread use, the effect of teleportation on proximity remains unexplored. To investigate this, we measured the interpersonal distance of 70 participants during interactions with embodied conversational agents, comparing teleportation to natural walking. Our findings revealed that participants maintained closer proximity from the agents during teleportation. Female participants kept greater distances from the agents than male participants, and natural walking was associated with higher agency and body ownership, though co-presence remained unchanged. We propose that differences in spatial perception and spatial cognitive load contribute to reduced interpersonal distance with teleportation. These findings emphasise that proximity should be a key consideration when selecting locomotion methods in social VR, highlighting the need for further research on how locomotion impacts spatial perception and social dynamics in virtual environments.
PUBLISHED
Keywords: Virtual Reality; Proximity; Locomotion; Distance Estimation; Creative Technologies; Digital Humanities; Embodied Conversational Agents; Human Computer Interaction; Proximity; Virtual Reality; Gender